The effect of health belief model-based short interviews in women in the postmenopausal period on the prevention of osteoporosis: A randomized controlled trial - KOLAÇ, NURCAN (My University, 2022)
Aim: This study was conducted to investigate the effect of health belief model-based short interviews on preventive behaviours for osteoporosis in postmenopausal women. Design and methods: A randomized pretest, posttest and follow-up design was used. The study was conducted between June 2016 and June 2017 with an intervention (n = 41) and a control group (n = 41). The intervention group applied the Short Interviews Model for 12 weeks as a short interview programme that was created based on the health belief model. The study data were collected by the researcher using a descriptive information form, the Osteoporosis Health Belief Scale, the Osteoporosis Self-efficacy Scale and the Osteoporosis Knowledge Test. Results: In the posttest and follow-up measurements, the mean scores of the intervention group on the total Osteoporosis Health Belief Scale and its self-efficacy and exercise sub-dimensions and the total Osteoporosis Knowledge Test and its subdimensions were significantly higher than those of the control group. Conclusion: The short interviews held in this study provided evidence to guide women and nurses in the prevention of osteoporosis in postmenopausal women. It is recommended that the prevention of osteoporosis should be integrated into women's health programmes at the primary health-care level.
Keywords: Tıp; Hemşirelik; Sağlık Bilimleri; Medicine; Nursing; Health Sciences; Klinik Tıp (MED); Klinik Tıp; HEMŞİRELİK; Clinical Medicine (MED); CLINICAL MEDICINE; NURSING; Genel Hemşirelik; General Nursing; 5A model short interviews; health belief model; nursing; osteoporosis; postmenopausal women; health belief model; nursing; osteoporosis; postmenopausal women; 5A model short interviews